2005
DOI: 10.1021/la050423k
|View full text |Cite
|
Sign up to set email alerts
|

Surface Structures, Photovoltages, and Stability of n-Si(111) Electrodes Surface Modified with Metal Nanodots and Various Organic Groups

Abstract: The surface structures, photovoltages, and stability of n-Si(111) electrodes surface-modified with Pt nanodots and organic groups were studied in an I-/I3- redox electrolyte, using alkyls of varied chain length and those having a double bond and ester at the terminal as the organic groups. The n-Si was first modified with the organic groups, and then Pt was electrodeposited on it. Linear sweep voltammetry revealed that, for the modification with alkyls, the overvoltage for the Pt deposition became significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 51 publications
1
30
0
Order By: Relevance
“…70,71 Interestingly, Takabayashi et al reported significant differences in catalyst dispersion on n-Si͑111͒ photoelectrodes modified with different alkyl surface moieties. 34 Irregular catalyst dispersion and low resultant energy-conversion efficiencies were reported with n-Si photoelectrodes modified by linear alkyl groups. We are currently exploring the use of unsaturated organic surface groups to provide ample sites for catalyst attachment while simultaneously controlling the underlying electrical surface passivation properties.…”
Section: Discussionmentioning
confidence: 99%
“…70,71 Interestingly, Takabayashi et al reported significant differences in catalyst dispersion on n-Si͑111͒ photoelectrodes modified with different alkyl surface moieties. 34 Irregular catalyst dispersion and low resultant energy-conversion efficiencies were reported with n-Si photoelectrodes modified by linear alkyl groups. We are currently exploring the use of unsaturated organic surface groups to provide ample sites for catalyst attachment while simultaneously controlling the underlying electrical surface passivation properties.…”
Section: Discussionmentioning
confidence: 99%
“…Multielectron transfer reactions at semiconductors are generally slow and a catalyst is required to efficiently promote these reactions. Hence, many groups have examined the modification of the semiconductor surface by catalytic metals 13–18. It was, however, found that direct contact of a metal leads to the formation of a Schottky junction and recombination center, resulting in a reduced efficiency 14.…”
Section: Methodsmentioning
confidence: 99%
“…It was, however, found that direct contact of a metal leads to the formation of a Schottky junction and recombination center, resulting in a reduced efficiency 14. Various attempts have been made to solve these problems by using particles instead of continuous metal15, 16 and separating the particles of catalytic metals from semiconductor surfaces by an organic molecular layer 17, 18. Unfortunately, however, the structure of organic layers and, therefore, the position and structure of the catalysts, are not well controlled.…”
Section: Methodsmentioning
confidence: 99%
“…For example, a monolayer with electron transfer function on Si is very important as far as the application for molecular devices, 10 sensors, 11 photoelectrochemistry, [12][13][14][15] bioelectrochemistry, 16 and electrocatalysis [13][14][15] are concerned. Organic monolayer can be formed on Si surface via direct Si-C bond utilizing thermal, [17][18][19][20][21][22][23] photochemical, 24,25 electrochemical, [26][27][28] or catalytic reaction 28,29 or reaction with radical initiators.…”
Section: Introductionmentioning
confidence: 99%
“…60 Nakato and colleagues also showed that the stability of the Si photoelectrode for I -oxidation was improved by Pt/alkyl monolayer modification. 13,14 Here, we investigated in detail the construction processes of organic monolayers with viologen moiety, not only with a monoviologen layer but also with multiviologen layers, on nand p-type Si(111) electrodes and the electrochemical characteristics of the modified n-and p-Si(111) electrodes in the dark and under illumination, respectively. After each modification step, surfaces were characterized by XPS, ellipsometry, and ATR FT-IR, and electrochemical characteristics were measured.…”
Section: Introductionmentioning
confidence: 99%